The Yoke of Linked Credit:A Study of Coastal Villages in Kanyakumari District, Tamil Nadu - Sahayaselvi, S. (Journal of Rural Development, 2014)
Almost in everyone’s life, credit becomes important as it serves as a shock-absorber in handling the difficulties of personal economy. In particular, it comes to be a life-support in the lives of fishermen because of the hazardous nature of their occupation, seasonal income and the paucity of funds. To maintain their trade and more often for their survival itself, the fishermen in the coastal sector of Kanyakumari district (study area) are found to be using both formal and informal credit sources. It has been found that the formal sources hardly lend down credit to these fishermen due to non-collateral security requirements, thus forcing the fishermen to have recourse to the informal sources for their credit needs which pushes the sample respondents’ either into market linked or labour linked credit. This type of credit binds the fishermen to sell their catch at under-pricing or under-weighing. As a consequence, result from 376 samples indicate that irrespective of the crafts they own, an average sample respondents’ economic position is reported to be low and they live in utter poverty with a hand to mouth situation. The fishermen, who borrow loans and advances, opt for this slow poison which has a stranglehold on them throughout their lives. This paper presents a number of recommendations for policy interventions to redress this danger and to uplift the economic condition of the fisherfolk who contribute 1.10 per cent to the Gross Domestic Product (GDP) of Indian economy.